Environment Preservation, Culture Maintenance, and Economy Improvement by Creatively Developing Traditional Cuisine into Modern Culinary Tourism Industry in Tegal - Atrinawati, Atrinawati (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
Environment preservation, culture maintenance, and economic improvement can be done by utilizing abundant local natural resources for traditional cuisine and using it as a tourist attraction in the form of traditional culinary tourism. This research shows how Tegal society utilize their farm and farming product for traditional cuisine as modern culinary tourism object. The data were collected by using folklore field research. The result shows that those efforts preserve the environment, maintain the culture, and improve the economy of Tegal society.Â